The Canadian Bureau for International Education: Innovator in the Higher Education Policy Landscape or Temporary Filler for Internationalization? 1966–2004 - Allison, John (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2026)
This article will examine the Canadian Bureau for International Education (CBIE). This non-governmental advocacy organization along with the Council of Ministers of Education, Canada (CMEC), and the Association of Universities and Colleges of Canada (AUCC, now Universities Canada) have been responsible for internationalizing higher education (HE) in Canada. It was and remains very significant to international higher education policy. This article will examine the history of the CBIE as it fills this important area of policy making in Canada. It will look critically at the early development of the organization, its fight for financial sustainability as a non-governmental organization (NGO), and lastly, its responses to continuing and emergent issues through to the 2000s. The need for an advocacy organization to fill this niche in Canadian international education policy continues today—what was the CBIE’s approach, and is the CBIE now a permanent fixture responsible for internationalizing higher education in Canada?